2009
DOI: 10.1063/1.3141481
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved photoluminescence spectroscopy of the initial oxidation stage of small silicon nanocrystals

Abstract: Articles you may be interested inTime-resolved and temperature-dependent photoluminescence of ternary and quaternary nanocrystals of CuInS2 with ZnS capping and cation exchange Photoluminescence of silicon nanoclusters with reduced size dispersion produced by laser ablation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 24 publications
(18 reference statements)
3
50
0
Order By: Relevance
“…25 On the other hand, luminescence enhancement has been observed after oxidation of Si-NCs produced by other methods, which has been attributed to an oxidation induced passivation of DBs. 11,14,15,30,[40][41][42][43][44] Distinct initial surface passivation and oxidation conditions may explain the apparent discrepancy between different studies. In an investigation where the oxidation approach of reducing the NCs size has been explored, the light emission of the smaller NCs obtained has been associated with defects, 1 in line with findings for Si nanocrystals embedded in amorphous SiO 2 , 45 and porous silicon.…”
Section: -35mentioning
confidence: 61%
See 2 more Smart Citations
“…25 On the other hand, luminescence enhancement has been observed after oxidation of Si-NCs produced by other methods, which has been attributed to an oxidation induced passivation of DBs. 11,14,15,30,[40][41][42][43][44] Distinct initial surface passivation and oxidation conditions may explain the apparent discrepancy between different studies. In an investigation where the oxidation approach of reducing the NCs size has been explored, the light emission of the smaller NCs obtained has been associated with defects, 1 in line with findings for Si nanocrystals embedded in amorphous SiO 2 , 45 and porous silicon.…”
Section: -35mentioning
confidence: 61%
“…29 In previous investigations of Si-NCs fabricated by other techniques, it has been found that oxidation may also result in a redshift of the NCs photoemission. 26,30,31 Theoretical calculations indicate that this could originate from the introduction of intragap energy levels by interfacial Si=O bonds, 26,27,32 and Si-O-Si surface bridges.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The PL emission observed in embedded films with both red and blue Si-NCs before thermal annealing is similar to that observed in the colloidal solutions (Figure 7a). Since the SOG around the Si-NCs is not chemically bonded to them, the embedded film emission is ascribed to the quantum confinement mechanism, as proposed by other authors for similar films [25,50]. The thermal annealing also appears to cause the loss of the H-passivated characteristics of the Si-NCs, modifying its configuration into an oxygen-passivated surface.…”
Section: Photoluminescence Propertiesmentioning
confidence: 60%
“…13,49,57,65,67,72,[125][126][127][128] The presence of Si surface radicals on Si NPs has been supported by electron paramagnetic resonance (EPR) spectroscopy, and various causes for their existence have been suggested. Two common causes that have been suggested are the formation of lowquality or disordered surface oxides, yielding EPR-active SiO 2 -Si, 56,72 and desorption of hydrogen from the H-Si NP surface, which yields EPR-active Si 3 -Si.…”
Section: Motivation For the Present Studymentioning
confidence: 99%